Efeito do ácido fólico no tratamento e prevenção do aumento gengival induzido por fenitoína: revisão de literatura seguida de metanálise - Faria, Rafael Correa de (2021)
Our systematic review and meta-analysis aims to summarize evidence on the effect of folic acid (FA) for the treatment and prevention of phenytoin-induced gingival overgrowth (PIGO). The literature search was conducted in PubMed, Embase, Cochrane Library, LILACS, Scopus, Web of Science and ClinicalTrials.gov databases, we also check in gray literature sources. We included randomized clinical trials involving people with epilepsy undergoing phenytoin monotherapy and with at least one group received FA to reduce or prevent of PIGO. We excluded studies that include participants with PIGO who have had other previous treatments, with incomplete or non-comparable data. We evaluated the intervention effect with the relative risk (RR) and 95% confidence interval (CI), we opted for the random effects model. To assess the risk of bias of the included studies, we used RoB 2.0 tool. We used GRADE to assess the certainty of the evidence. Initially, we identified 366 articles and only five randomized controlled clinical trials met the inclusion criteria, of which we had a total of 246 participants. FA did not show benefits for treatment (RR 1.50; 95% CI: 0.92; 2.43; Pvalue = 0.1) and for prevention of PIGO (RR 1.96; 95% CI: 0.55; 6.96; Pvalue = 0.3). We conclude that FA therapy is not effective for the treatment and prevention of PIGO.